2004
DOI: 10.1161/01.cir.0000138946.29375.49
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Matrix Metalloproteinase Activity by TIMP-1 Gene Transfer Effectively Treats Ischemic Cardiomyopathy

Abstract: Background-Enhanced activity of matrix metalloproteinases (MMPs) has been associated with extracellular matrix degradation and ischemic heart failure in animal models and human patients. This study evaluated the effects of MMP inhibition by gene transfer of TIMP-1 in a rat model of ischemic cardiomyopathy. Methods and Results-Rats underwent ligation of the left anterior descending coronary artery with direct intramyocardial injection of replication-deficient adenovirus encoding TIMP-1 (nϭ8) or null virus as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 32 publications
2
35
1
1
Order By: Relevance
“…22 Conversely, adenovirus-mediated expression of TIMP-1 was reported to mitigate the severity of ischemic injury. 39 These data suggested that TIMP-1 might exert a protective effect in the myocardium, consistent with the concept that increased MMP activity is a key process driving myocardial pathology after myocardial infarction or stress-related injuries 13,32 ; by this reasoning, expression of TIMP-1 is a physiological response that counterbalances MMP proteolysis, 14,40,41 and TIMP-1 blockade should, in theory, exacerbate disease. We show here that TIMP-1 expression in the heart increases during viral myocarditis, consistent with many studies that show that TIMP-1 is up-regulated in response to myocardial injury.…”
Section: Discussionsupporting
confidence: 72%
“…22 Conversely, adenovirus-mediated expression of TIMP-1 was reported to mitigate the severity of ischemic injury. 39 These data suggested that TIMP-1 might exert a protective effect in the myocardium, consistent with the concept that increased MMP activity is a key process driving myocardial pathology after myocardial infarction or stress-related injuries 13,32 ; by this reasoning, expression of TIMP-1 is a physiological response that counterbalances MMP proteolysis, 14,40,41 and TIMP-1 blockade should, in theory, exacerbate disease. We show here that TIMP-1 expression in the heart increases during viral myocarditis, consistent with many studies that show that TIMP-1 is up-regulated in response to myocardial injury.…”
Section: Discussionsupporting
confidence: 72%
“…Selective inhibition of TIMP-1 in TIMP-1 knockout mice has also been shown to exacerbate left ventricular remodelling after AMI (48). The role of TIMP-1 activity alteration was confirmed by Jayasankar et al (49), who demonstrated that in left coronary artery ligation-induced MI in rats, TIMP-1 gene transfer inhibited MMP activity, and preserved cardiac function and geometry in ischemic cardiomyopathy.…”
Section: Mmp Inhibitors and Ami In Animal Modelsmentioning
confidence: 90%
“…For instance, gene transfer of TIMP1 reduced matrix metalloproteinase activity 6 wk after left anterior descending artery occlusion, preserved both systolic and diastolic function, and reduced myocardial fibrosis (407). Overexpression of IB also improved end-diastolic and systolic function after infarction (894).…”
Section: Other Signaling Targetsmentioning
confidence: 99%